Mapping and Analiyzing The Level of Road Damage Using Geographic Information System Applications (Case Study : Srandakan-Poncosari-Pandansimo Road, Srandakan Sub-District, Bantul, Special Region of Yogyakarta) - Jamal, Jamal; Wahyudiono, Wahyudiono; Darma, Demmy Adhi Mulya (Dinasti Research, 2025)
The Srandakan-Poncosari-Pandansimo road section, Srandakan District, Bantul Regency, Yogyakarta Special Region Province is a road that connects Bantul City with tourism sites. Based on its function, the Srandakan-Poncosari-Pandansimo road section is included in the Provincial road category. In order for the road to be used properly, the road must be made and designed and maintained in accordance with the requirements set by the government. Road pavement is a layer of pavement that lies between the subgrade and the wheels of the vehicle. There are three types of pavement, namely flexible, rigid and composite or combined pavement. Geographic Information System is a spatial information technology system that is commonly used today. In general, GIS works based on five components, namely hardware, software, data, people, and methods. The selection of data methods using GIS because of the ability of GIS programs that can answer the needs of efficient information systems and are able to process data with complex structures and geographic (spatial) based. GIS is able to store, analyze, present spatial data and atri but data (tables), able to answer spatial questions (how long, wide etc.) so as to provide more informative data than other computer-based information systems and can help make decisions quickly and accurately. In this study, the percentage of road damage is 3.110345%. The types of damage on the Srandakan-Poncosari-Pandansimo road section are longitudinal cracks, random cracks, alligator cracks, potholes, collapse or deformation and patches.